1993
DOI: 10.1007/bf01225234
|View full text |Cite
|
Sign up to set email alerts
|

The application of selected histochemical and immunohistochemical markers and procedures to the diagnosis of early myocardial damage

Abstract: Histochemical (= HIS) methods (haematoxylin-eosin, luxol fast blue, chromotrope aniline blue) and various immunohistochemical (= IH) markers (myoglobin, desmin, fibrinogen, complement C5b-9) were applied in parallel to test the efficiency, specificity and sensitivity for the recognition of early ischemic myocardial damage. The whole series was subgrouped into cardiac deaths (N = 35) and controls (N = 13). Cardiac deaths were sub-divided into 3 groups: 1. infarction visible in gross examination (N = 15), 2. cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 20 publications
3
37
0
1
Order By: Relevance
“…In the present study, the only myocardial lesion found corresponded to "contraction band necrosis" or "coagulative myocytolysis" or "Zenker necrosis": the two latter terms prove to be more precise due to the presence of different types of contraction bands and they indicate a necrosis of the myocardial cells in a hypercontracted state (tetanic death) characterised by rhexis of the myofibrillar apparatus, anomalous hypereosinophilic cross-bands formed by segments of hypercontracted sarcomeres with extremely thickened Z lines, as shown ultrastructurally [32,33,34,35]. Within chronological limits, the present findings confirm the conclusions of the previous human study [7]: a. Cocaine-related adrenergic overactivity does not induce extensive myocardial necrosis and thus per se is unable to explain the cardiac arrest.…”
Section: Morphological Findingsmentioning
confidence: 95%
“…In the present study, the only myocardial lesion found corresponded to "contraction band necrosis" or "coagulative myocytolysis" or "Zenker necrosis": the two latter terms prove to be more precise due to the presence of different types of contraction bands and they indicate a necrosis of the myocardial cells in a hypercontracted state (tetanic death) characterised by rhexis of the myofibrillar apparatus, anomalous hypereosinophilic cross-bands formed by segments of hypercontracted sarcomeres with extremely thickened Z lines, as shown ultrastructurally [32,33,34,35]. Within chronological limits, the present findings confirm the conclusions of the previous human study [7]: a. Cocaine-related adrenergic overactivity does not induce extensive myocardial necrosis and thus per se is unable to explain the cardiac arrest.…”
Section: Morphological Findingsmentioning
confidence: 95%
“…In each case, immunohistochemical reactions with the antibodies fibronectin (Polyclonal Rabbit Anti-Human, DAKO Deutschland GmbH, Hamburg, Germany) and C5b-9 (Monoclonal Mouse Anti-Human, DAKO Deutschland GmbH, Hamburg, Germany) of both cardiac ventricles (free wall of the right ventricle (RV), anterior and/or posterior wall of the left ventricle (LV)) were prepared as described elsewhere [13,14]. A blind investigation of the slides was performed by two different observers with final consensual evaluation.…”
Section: Immunohistochemical Reactionsmentioning
confidence: 99%
“…The finding of contraction band necrosis, even if microfocal, could be an important histological signal for interpreting the cause of death and the natural history of a disease in any single patient. In particular, in a sudden death resulting from myocardial infarction that is otherwise not detectable histologically (26)(27)(28), the finding of contraction band necrosis could be the marker explaining cardiac arrest as secondary to adrenergic stress. However, one must remember that in people who die suddenly and unexpectedly, the frequency of a myocardial infarction is about 20% as shown in resuscitated and electrocardiographically monitored patients (9).…”
Section: The Myocardial Alterationmentioning
confidence: 95%